The origin of efficient triplet state population in sulfur-substituted nucleobases - Sebastian Mai (Nature Portfolio, 2016)
Sulfur-substituted nucleobases are promising photo- and chemotherapeutic drugs. Here, the authors unravel the electronic and structural aspects that lead to the ultrafast population of triplet states in these molecules, providing an explanation for their efficiency as photosensitizers.